1999
DOI: 10.1128/jvi.73.3.2126-2135.1999
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Integrase Protein Promotes Reverse Transcription through Specific Interactions with the Nucleoprotein Reverse Transcription Complex

Abstract: The human immunodeficiency virus type 1 (HIV-1) integrase protein (IN) is essential for integration of the viral DNA into host cell chromosomes. Since IN is expressed and assembled into virions as part of the 160-kDa Gag-Pol precursor polyprotein and catalyzes integration of the provirus in infected cells as a mature 32-kDa protein, mutations in IN are pleiotropic and may affect virus replication at different stages of the virus life cycle in addition to integration. Several different phenotypes have been obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 183 publications
(77 citation statements)
references
References 59 publications
2
75
0
Order By: Relevance
“…This suggests an effect of the integrase enzyme on events proximal to the reverse transcription that determine proper and efficient initiation of viral DNA synthesis. Very recently, Wu et al 55 demonstrated the importance of the highly conserved HisHisCysCys-motif of the mature integrase protein for efficient initiation of reverse transcription.…”
Section: Other Viral Proteinsmentioning
confidence: 99%
“…This suggests an effect of the integrase enzyme on events proximal to the reverse transcription that determine proper and efficient initiation of viral DNA synthesis. Very recently, Wu et al 55 demonstrated the importance of the highly conserved HisHisCysCys-motif of the mature integrase protein for efficient initiation of reverse transcription.…”
Section: Other Viral Proteinsmentioning
confidence: 99%
“…Like Tat, IN is required for efficient RTN initiation [39,106]. Interestingly, IN enzymatic activity is not required for this function since mutations in the highly conserved D 64 D 116 E 152 catalytic domain permit RTN, and inhibitors that block IN activity do not inhibit initiation in NERT [59].…”
Section: Tat and Integrase Have Roles In Reverse Transcriptionmentioning
confidence: 99%
“…It is likely that an early RTN complex associates with cytoskeletal proteins [36], and during trafficking to the nucleus reorganises into a pre-integration complex containing proviral DNA, IN and Vpr. As IN directly binds to RT [106], IN may be a legitimate component of the RTNIC.…”
Section: Tat and Integrase Have Roles In Reverse Transcriptionmentioning
confidence: 99%
“…There have been several pieces of evidence suggesting the existence of direct and indirect interactions between HIV-1 IN and RT [4,5]. Direct physical interactions occur as RT binds to the Cterminal domain (CTD) of IN [6,7] genome yields non-integrated DNA [8]; indeed, non-integrated DNA levels can reach 99% of total viral DNA at the asymptomatic phase of infection [9]. This non-integrated DNA has full capacity to synthesize all classes of viral transcripts, both spliced and non-spliced, prior to integration [8,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Indirect interaction between IN and RT occurs as the product of RT-catalyzed reactions binds to the IN protein. In vitro studies with purified IN and RT have shown that HIV-1 IN can indirectly stimulate both the initiation and elongation modes of RT-catalyzed reverse transcription by enhancing RT processivity[7]. However, how these two key viral enzymes coordinate viral DNA production by affecting each other activity is still poorly understood.…”
mentioning
confidence: 99%